Microstructural analysis and mechanical properties of Ni35Co25.5Al16Fe15.5Cr8 high-entropy alloy in the as-cast and homogenized conditions - A. Pourferiedouni; S.G. Shabestari (Journal of Materials Research and Technology)
In the present work, a non-equimolar hypoeutectic Al–Co–Cr–Fe–Ni high-entropy alloy (HEA) with FCC lattice structure phase matrix and the eutectic compound was prepared via vacuum arc remelting (VAR) followed by homogenized at 1200 °C for 20 h to minimize microsegregation. The as-cast alloy exhibited a dual-phase microstructure, consisting of a primary FCC (face-centered cubic) phase and an interdendritic eutectic region containing both FCC/BCC (body-centered cubic) phases. After homogenization, the eutectic structure was eliminated, resulting in a (Ni, Al)-rich BCC phase in the interdendritic regions. Mechanical properties were assessed using compression test, hardness, and small punch test (SPT) equipment. The true compression strength of homogenized samples exceeded 1300 MPa while the true compression strength of the as-cast sample was over 1130 MPa. The estimated ultimate strength obtained using the SP method is approximately 840 MPa for the homogenized sample, compared to 644 MPa for the as-cast sample. Finite element simulations of the small punch test were conducted to validate the experimental results. FE analysis revealed that the maximum stress was localized near the center of the sample and spread outward. Fracture surface analysis of SPT samples showed radial cracks on the hemispherical surface. Dimples adjacent to cleavage indicated quasi-cleavage fractures in both as-cast and homogenized samples. This study highlights the critical role of homogenization in enhancing the mechanical properties and microstructural stability of Ni-based HEAs, contributing to the development of high-strength materials for advanced structural applications.